Winter habitat selection by female moose in southwestern Montana and effects of snow and temperature. Issue 5 (10th August 2022) - Burkholder, Braden O.; Harris, Richard B.; DeCesare, Nicholas J.; Boccadori, Sylvanna J.; Garrott, Robert A.
Abstract : Moose Alces alces are among the many species that are vulnerable to both direct and indirect effects of climate change. Habitat selection is one framework to assist investigators in disentangling the various factors (including weather) that ultimately dictate how animals respond to their environment. We investigated patterns of winter habitat selection by adult female moose in southwestern Montana, USA during 2007–2010, and how that selection was affected by snow (quantified by snow water equivalent) and winter temperatures. We used data from GPS collars and a suite of environmental covariates to quantify winter habitat selection at both study area (2nd order) and home range (3rd order) spatial scales using resource selection functions. Moose strongly selected for the willow ( Salix spp.) cover type, and against grassland cover. Moose use of conifer cover at the home range scale increased when either amount of snow or ambient temperature was higher, although the latter only during periods of the day when conifer patches were likely to have been cooler than cover types lacking a canopy. Wildlife conservation and management naturally focuses on preferred habitats, particularly those that fulfill essentially all foraging requirements. However, habitats used preferentially under stressful weather conditions, even if used rarely overall, can also form a critical part of a species' overall needs.